Isolasi dan Identifikasi Steroid dari Ekstrak N-Heksana Daun Afrika (Vernonia amygdalina Del.): Isolation and Identification of Steroid from N-Hexane Extract of Vernonia amygdalina Del. - Erwin; Evi Mashunah; Saibun Sitorus (Chemistry Department, Mathematics and Natural Science Faculty, Tadulako University, 2020)
Isolation and identification of steroids from the n-hexane fraction of Vernonia amygdalina Del. was carried out. Separation and purification were performed using flash chromatographic and gravity chromatography. Based on the results of phytochemical tests supported by UV and FT-IR data analysis, the isolate obtained was a steroid (sterol type). Toxicity test results using the Brine Shrimp Lethality Test (BSLT) were known that the steroid has moderate toxicity with an LC50 value of 48.39 ppm. Keywords: Vernonia amygdalina Del., Toxicity, BSLT, Sterol, Steroid